Multitarget Stool DNA Screening in Clinical Practice: High Positive Predictive Value for Colorectal Neoplasia Regardless of Exposure to Previous Colonoscopy. (17th April 2020) - Eckmann, Jason D.; Ebner, Derek W.; Bering, Jamie; Kahn, Allon; Rodriguez, Eduardo; Devens, Mary E.; Lowrie, Kari L.; Doering, Karen; Then, Sara; Burger, Kelli N.; Mahoney, Douglas W.; Prichard, David O.; et al.
Abstract : OBJECTIVES: Multitarget stool DNA (MT-sDNA) testing has grown as a noninvasive screening modality for colorectal cancer (CRC), but real-world clinical data are limited in the post-FDA approval setting. The effect of previous colonoscopy on MT-sDNA performance is not known. We aimed to evaluate findings of colorectal neoplasia (CRN) at diagnostic colonoscopy in patients with positive MT-sDNA testing, stratified by patient exposure to previous colonoscopy. METHODS: We identified consecutive patients completing MT-sDNA testing over a 39-month period and reviewed the records of those with positive tests for neoplastic findings at diagnostic colonoscopy. MT-sDNA test positivity rate, adherence to diagnostic colonoscopy, and the positive predictive value (PPV) of MT-sDNA for any CRN and neoplastic subtypes were calculated. RESULTS: Of 16, 469 MT-sDNA tests completed, testing returned positive in 2, 326 (14.1%) patients. After exclusion of patients at increased risk for CRC, 1, 801 patients remained, 1, 558 (87%) of whom underwent diagnostic colonoscopy; 918 of 1, 558 (59%) of these patients had undergone previous colonoscopy, whereas 640 (41%) had not. Any CRN was found in 1, 046 of 1, 558 patients (PPV = 67%). More neoplastic lesions were found in patients without previous colonoscopy (73%); however, the rates remained high among those who had undergone previous colonoscopy (63%, P < 0.0001). The large majority (79%) of patients had right-sided neoplasia. DISCUSSION: MT-sDNA has a high PPV for any CRN regardless of exposure to previous colonoscopy. Right-sided CRN was found at colonoscopy in most patients with positive MT-sDNA testing, representing a potential advantage over other currently available screening modalities for CRC.